The effects of kinematic variables and sequence during horizontal bar swing in gymnastic: a case study - Park, S.; Kim, S.-J.; Song, J.-W.; Jo, S.-M.; Song, J. (Korean Journal of Sport Biomechanics, 2023)
Objective: The horizontal bar of gymnastics is fundamentally based on rotational movements. This study aimed to determine the effect of kinematics variables and sequence during horizontal bar performance (Kovacs, Tkatchev Stretched & Kolman) in gymnastic. Method: Four gymnastics athletes of the national team were participated in this study. All subjects were asked to perform the three types of horizontal bar skill. Simi marker-less cameras were used to collect the raw data (120 Hz). Kinematic variables (total time, interval, center of mass, height, angular velocity etc.) and sequence variables were calculated to examine the differences. Results: As a result, horizontal bar performance in gymnastic has special sequence that making the peak angular velocity from distal joint to proximal joint (knee-hip-shoulder). It is rare sequence that typical sport does not have. Conclusion: In field, gymnastic coaches and players should know the result that there is special sequence in horizontal bar performance. It could be very useful to teach and enhance their performance.